Essays in empirical labor economics and alternative finance - Sierra, M (2017)
This thesis consists of three independent chapters. The first two chapters are motivated by an empirical fact: most countries in Latin America experienced sharp changes in the wage structure since the mid-1990s, characterised by a substantial reduction of earnings inequality. At the same time that inequality was falling, the economies in the region experienced a rapid transformation of the age, education, and gender composition of their workforces. To what extent are these two phenomena interconnected? Did the wage structure changed as a consequence of the recomposition of labor supply? To answer these questions I propose two stylized models of the labor market, and estimate their main parameters using household survey data ranging more than two decades from Argentina, Brazil, Chile and Mexico. I provide evidence that supply side trends are the major driver of the observed patterns in relative earnings. While relative demands favoured high-skilled workers during the 1990s, they shifted in favour of low-skilled workers during the 2000s. In the third chapter the subject matter changes altogether. Here I will focus on the workings of newly developed financial technologies used by entrepreneurs to raise capital for their businesses. In particular, the rapidly growing equity crowdfunding market is analysed. The chapter is motivated by the concerns of analysts and regulators that crowdfunding markets are vulnerable to investment herding, so that prior investors' decisions induce future investors to make similar choices. We develop a stylised model to answer the following question: how should herding be characterised in an equity crowdfunding setting where much of the inter-temporal information about a project is based on the amounts previously invested? The model generates predictions that we test using a unique investment-level dataset from one of the leading UK equity crowdfunding platforms. We provide evidence of a considerable level of immediate inter-temporal herding on an equity crowdfunding platform that, nevertheless, quickly dissipates.